Visual Politics in the Global South
XXIII, 331 p. 47 illus., 26 illus. in color.
Keywords: This collection is an essential contribution to the growing field of visual political communication, encouraging scholarly dialogue and recognition for a variety of ‘global-south approaches’ to visual politics. The editors bring together a diverse set of essays on both official political campaigning and grassroots protest politics, with each study examining a specific kind of visuality or visibility across varied cultural contexts. Katy Parry, Associate Professor in Media and Communication, University of Leeds, UK Visuals take centre stage in this thorough, timely and telling volume that captures all we need to know about how images are shaping the development of politics in the Global South. Long overdue, the editors ought to be congratulated for their outstanding vision in choosing non-Western societies as a focus of their study on political phenomena in the era of visual imagery. Bruce Mutsvairo, Professor and Chair, Media, Politics and the Global South, Utrecht University, the Netherlands. This is an urgently needed book that pushes for the de-Westernisation and decolonisation of the study of visual politics. What makes the collection especially compelling is how it, well, makes visible the rich diversity of visual politics research in the global South. Jason Vincent A. Cabañes, Professor of Communication, De La Salle University, Philippines It is widely acknowledged that the production, dissemination and consumption of visual products in the Global South is powerfully shaped by geo-politics and a power dynamics in which the Global North dominates the South. However, little is known about the ways in which scholarship in the Global South might challenge and resist western approaches to the study of the visual. Against this background, this book examines visual politics in the Global South through theoretically driven, and empirically grounded case studies, which focus onthe role of the visual in formal politics (e.g., political campaigns) and everyday politics (e.g grassroots politics, civil society initiatives). It will be of interest to both researchers and students interested in the study of visual politics from various disciplinary lens (media and communication, anthropology, politics, and sociology). Anastasia Veneti is Principal Academic at the Faculty of Media and Communication, Bournemouth University, UK. Maria Rovisco is Associate Professor in Sociology at the School at the School of Sociology and Social Policy at the University of Leeds, UK.